2021
DOI: 10.3389/fphar.2021.633447
|View full text |Cite
|
Sign up to set email alerts
|

Active Components and Pharmacological Effects of Cornus officinalis: Literature Review

Abstract: Cornus officinalis Sieb. et Zucc. (Shanzhuyu), a herb and food plant in east Asia, has the properties of tonifying the liver and kidney, and nourishing the essence according to the theory of traditional Chinese medicine. C. officinalis has been commonly used to treat asthenia diseases, liver, and kidney diseases, and reproductive system diseases since ancient times. The objectives of this article were to review the pharmacological effects and phytochemistry of C. officinalis. We conducted a literature review o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 90 publications
0
45
0
Order By: Relevance
“…The CM used in these cohorts mostly contained a classical CM formulation, namely, Rehmannia-6 complex (R-6, Liu-wei-di-huang-wan) with variations according to the symptom-based diagnosis. R-6 contains Rehmanniae Radix (Di-huang) ( Yokozawa et al, 2004 ), Corni Fructus (Shan-zhu-yu) ( Gao et al, 2021 ), Dioscoreae Rhizoma (Shan-yao) ( Luo, 2008 ), Poria (Fu-ling) ( Sun, 2014 ), Moutan Cortex (Mu-dan-pi) ( Wang et al, 2017b ), and Alismatis Rhizoma (Ze-xie) ( Zhang et al, 2017a ). According to classical CM theory, R-6 replenishes the kidney and clears the waste including fluid retention.…”
Section: Introductionmentioning
confidence: 99%
“…The CM used in these cohorts mostly contained a classical CM formulation, namely, Rehmannia-6 complex (R-6, Liu-wei-di-huang-wan) with variations according to the symptom-based diagnosis. R-6 contains Rehmanniae Radix (Di-huang) ( Yokozawa et al, 2004 ), Corni Fructus (Shan-zhu-yu) ( Gao et al, 2021 ), Dioscoreae Rhizoma (Shan-yao) ( Luo, 2008 ), Poria (Fu-ling) ( Sun, 2014 ), Moutan Cortex (Mu-dan-pi) ( Wang et al, 2017b ), and Alismatis Rhizoma (Ze-xie) ( Zhang et al, 2017a ). According to classical CM theory, R-6 replenishes the kidney and clears the waste including fluid retention.…”
Section: Introductionmentioning
confidence: 99%
“…Cornus officinalis ( C. officinalis ), the dry mature fruit of C. officinalis Siebold & Zucc, is redefined as a class of herb and edible plant and has been commonly used in traditional Chinese medicine (TCM) ( 1 ). C. officinalis with mild warm nature, belongs to the meridians of the liver and kidney according to TCM theory; thus, it is commonly used in the prevention and treatments of liver and kidney diseases ( 2 ). Moreover, it can be found in foodstuff, such as medicinal dishes, healthcare products, and drinks due to its various pharmacological activities, including anti-inflammatory, antioxidant, and anti-apoptotic ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…is classified as a tonic in traditional Chinese medicine. There are various biologic active compounds, including iridoids, tannins, flavonoids, polysaccharides, triterpenoids, ursolic acid and organic acid esters, are present in Cornus officinalis [1][2][3]. Pharmacological studies have revealed that the Cornus officinalis possesses the effects of being anti-neoplastic, hypoglycemic, enhancing sperm motility, antioxidation and being anti-inflammatory [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%